Objects of environmental legal relations: discussion aspects - Makarova, Tamara I.; Lizgaro, Viсtoria E. (Journal of the Belarusian State University. Law, 2024)
Legal approaches of a conceptual nature to determining the object of environmental legal relations are explored in the context of the adoption of a new edition (2023) of the Law of the Republic of Belarus of 26 November 1992 No. 1982-XII «On environmental protection». It is proposed to consider the object of environmental legal relations from the point of view of the simultaneous presence of natural as well as material properties as leading features enshrined in regulatory legal acts, taking into account the fact that their list has been adjusted in the latest legislation. The criteria for determining the range of objects of environmental legal relations are substantiated. Proposals aimed at improving the legal regulation in the area under study are formulated.
Keywords: environmental law; environment; environmental legal relations; object of environmental legal relations